Analysis of Open Mine Drainage System in Coal Mining Area Block A PT. Minemex Indonesia Site Mandiangin, Sarolangun Regency, Jambi Province - Azmi Abdulah Binolombangan,; Hendro Purnomo,; Shilvyanora Aprilia Rande, (ReTII, 2023)
PT. Minemex Indonesia is a coal mining company that implements an open-pit mining system. The open-pit mining method is strongly influenced by weather factors, especially the rainy season. When there is high intensity rain, it will increase the volume of water accumulated at the bottom of the mine. Block A mine drainage systems are mine drainage and mine dewatering. The method in the mine drainage system analysis effort is by processing primary data of drainage component dimensions and secondary data of rainfall data for the last 11 years using Gumbell and Mononobe distributions. Analysis of rainfall data for 2011-2021, obtained rainfall for the 5-year anniversary period of 100.90 mm/day. The rainfall intensity based on the highest duration is 22.04 mm/hour. The area of DTH based on the mining situation map in August 2022 is 75.9363 Ha. Rainwater discharge was obtained at 14.57 m3/hour, runoff water discharge of 11,088 m3/hour, and groundwater discharge of 0.399 m3/hour. The pumps used are 2 units (Ksb 150 and 200), each discharge of 400 m3/hour and 550 m3/hour. The dimensions of the open channel are known to be adequate, able to accommodate the incoming water discharge in the channel. The sump volume of mine progress in August 2022 amounted to 17,348.25 m3, known to be adequate. The total area of the settling pond is 3,138.4 m2 and the total volume is 6,058.9 m3, not sufficient enough so that dimensional improvements are needed. Keywords : Discharge, Channel, Sump, Settling Pond